Coexistence of multibacillary Hansen’s disease and pulmonary tuberculosis in a patient with type 2 diabetes mellitus: A diagnostic and therapeutic challenge. - Bibhuti Nayak; Sudarsan Pothal (International Journal For Multidisciplinary Research, 2026)
Background: The coexistence of Hansen’s disease and pulmonary tuberculosis is uncommon despite both diseases being highly endemic in India. Impaired cell-mediated immunity associated with multibacillary Hansen’s disease and diabetes mellitus may increase susceptibility to dual mycobacterial infection, posing significant diagnostic and therapeutic challenges. Case Presentation: A 50-year-old male with poorly controlled type 2 diabetes mellitus diagnosed case of Hansen’s disease on multidrug therapy (MDT) with history of Type I (reversal) lepra reaction presented with low-grade intermittent fever, productive cough, anorexia, generalized weakness, and weight loss. Chest radiography revealed bilateral pulmonary infiltrates. Sputum examination by Cartridge-Based Nucleic Acid Amplification Test (CBNAAT) detected Mycobacterium tuberculosis without rifampicin resistance, confirming pulmonary tuberculosis. The patient was started on anti-tubercular therapy under the National Tuberculosis Elimination Programme while continuing MDT for Hansen’s disease, with subsequent clinical improvement. Conclusion: This case underscores the importance of maintaining a high index of suspicion for tuberculosis in patients with Hansen’s disease, particularly in the presence of diabetes mellitus and lepra reactions. Early diagnosis using molecular techniques and prompt initiation of appropriate therapy are crucial to prevent treatment delays, inappropriate rifampicin exposure, and adverse clinical outcomes.